1992
DOI: 10.1080/07399339209516016
|View full text |Cite
|
Sign up to set email alerts
|

Work, marital status, and heart disease

Abstract: Longitudinal data from the U.S. National Health and Nutrition Survey and its follow-up were used to analyze the effects of marriage and work roles and changes in these roles on the incidence of coronary heart conditions in a sample of 3,097 middle-aged women. Education, age, family income, race, and number of children were included as covariates. The data indicated that women who became unmarried, younger women, and better educated women were at relatively low risk, whereas women who left the labor force and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…Several factors may account for the contrasting results observed in that study including different participant composition (all white), the inclusion of angina in the definition of CHD, and an earlier time period (1960s) when the transition of married women into the work force was in the beginning stages 14. Our finding of a decreased risk of CHD events (fatal and non-fatal) among women employed outside of the home is comparable to the previous finding reported by Reviere et al13 of a higher risk of CHD among homemakers. The association observed in our study did not vary for fatal or non-fatal events but it persisted after adjustment for socioeconomic and cardiovascular factors.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Several factors may account for the contrasting results observed in that study including different participant composition (all white), the inclusion of angina in the definition of CHD, and an earlier time period (1960s) when the transition of married women into the work force was in the beginning stages 14. Our finding of a decreased risk of CHD events (fatal and non-fatal) among women employed outside of the home is comparable to the previous finding reported by Reviere et al13 of a higher risk of CHD among homemakers. The association observed in our study did not vary for fatal or non-fatal events but it persisted after adjustment for socioeconomic and cardiovascular factors.…”
Section: Discussionsupporting
confidence: 68%
“…In the Tecumseh Study, self-reported heart attacks were greater among homemakers, although no difference in diagnosed CHD was noted between employed women and homemakers 12. Also, homemakers had an increased risk of CHD in the National Health and Nutrition Survey 13, while no difference in CHD incidence between employed women and homemakers was reported in the Framingham Study 14.…”
Section: Introductionmentioning
confidence: 86%
“…17,47,48 Relatedly, we also suspect that a history of divorce may have had negative consequences for medication adherence, healthcare utilization, and disease management that may have precipitated or worsened vascular pathology. 15,18,49,50 Accordingly, studies have shown that spouses (particularly wives) encourage concordant health behaviors—such as proper diet, exercise, and medication compliance—that promote cardiovascular health. 30-32 Therefore, we encourage future studies to explore these mechanisms to help explain how repeated exposure to divorce incurs increasing risks for AMI.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although studies have shown that divorce is a major life stressor linked to poor health outcomes, 11-17 research has focused almost entirely on the cross-sectional risks related to current marital status and have largely ignored lifetime exposure to divorce and its potential consequences for the cardiovascular health of men and women. 13,16,18-23 …”
mentioning
confidence: 99%
“…[5][6][7] The literature to date examining the association between women's employment status and CVD and mortality has been inconsistent. Reviere et al 8 reported homemakers were more likely to be diagnosed with coronary heart disease (CHD) than employed women. In contrast, there was no difference in the rate of diagnosed CHD between the employed women and homemakers in the Tecumseh Study, and self-reported occurrence of heart attacks was higher among homemakers than employed women.…”
Section: Introduction Wmentioning
confidence: 99%